Across the Boundary: The Formalization of the Interface Between Episodic Memory and Narrow Syntax Computation of Human Language - Edward Ruoyang Shi (Biolinguistics)
A growing number of studies indicate that the hippocampus plays an essential role in language processing as well as episodic memory. However, there is no consensus on how it is engaged in both domains and how it connects the two domains. From a theoretical perspective, this paper delves into the intricate relationship between episodic memory and the narrow syntax of human language. To be more specific, I focus on the functions of the hippocampus in event processing and propose that hippocampal phasic activity supports the cyclic interaction between episodic memory and narrow syntax. Through such cyclic interaction, the event in the episodic memory is assigned a linguistic format that can be communicated, while narrow syntax is provided with an interpretative engine that underlies reference. This hypothesis predicts that when episodic memory is impaired, corresponding abnormalities appear in linguistic reference.